2021
DOI: 10.1007/s10570-021-03713-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences and similarities between kraft and oxygen delignification of softwood fibers: effects on chemical and physical properties

Abstract: The fiber properties after oxygen delignification and kraft pulping were studied by looking into the chemical characteristics and morphology. The effect of the two processes on the fibers was evaluated and compared over a wider kappa number range (from 62 down to15). Wide-angle X-ray scattering, nuclear magnetic resonance and fiber saturation point were used to characterize the fiber network structure. Fiber morphology and fiber dislocations were evaluated by an optical image analysis. The total and surface fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…(2013) decreased the kappa number of eucalyptus pulps by 0.5-1.5 units when alkali leaching was performed at 90 C for 90 min. For spruce pulps, a kappa number reduction of 3-4 units was obtained at 100 C for 30 min (Esteves et al 2021). This together with the present study shows that the residual alkali level has only a minor effect on lignin re-precipitation.…”
Section: Washing Of Pulp Bressupporting
confidence: 78%
“…(2013) decreased the kappa number of eucalyptus pulps by 0.5-1.5 units when alkali leaching was performed at 90 C for 90 min. For spruce pulps, a kappa number reduction of 3-4 units was obtained at 100 C for 30 min (Esteves et al 2021). This together with the present study shows that the residual alkali level has only a minor effect on lignin re-precipitation.…”
Section: Washing Of Pulp Bressupporting
confidence: 78%
“…However, it has been shown that oxygen can improve the mechanical strength of paper (Esteves et al 2020;Snowman et al 1999;Yang et al 2003;Zhang et al 2005) even if fiber deformation occurs. Fiber deformation can be due to an increased fiber vulnerability after cooking and defibration and not to the oxygen delignification (Esteves et. al.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that fibers with a high internal integrity (higher lignin and less mechanical processes/steps) show a greater resistance to expansion and therefore less swelling development (Stone et al 1971). After the individualization of the fibers by defibration process after kraft cook they may be more susceptible to subsequent treatment (Esteves et. al.…”
Section: Fiber Charge: Effect On Refinability and Mechanical Propertiesmentioning
confidence: 99%
“…Because the influence of solvents in the C60/C70 solution and hydrosols could be avoided, the dried, coated gold showed a high SERS activity [ 199 , 200 ]. The SERS subtract intensity of most peaks of colloidal Au coatings increased and then slowly decreased depending on the saturation [ 201 , 202 ].…”
Section: Applications Of Cellulosementioning
confidence: 99%